Composition of the surgical team in aortic arch surgery—a risk factor analysis. (25th March 2022) - Berger, Tim; Kreibich, Maximilian; Rylski, Bartosz; Schibilsky, David; Pooth, Jan-Steffen; Fagu, Albi; Zimmer, Emmanuel; Pingpoh, Clarence; Beyersdorf, Friedhelm; Czerny, Martin; Siepe, Matthias
Abstract: OBJECTIVES: The aim of this study was to analyse the influence of varying experiences within each surgical team to identify team-related risk factors on clinical outcomes after total aortic arch replacement. METHODS: Each surgeon was rated from 1 to 5, and a surgical team's score was calculated (operating surgeon + assisting surgeon = team score) by relying on each member's experience. A composite end point (mortality, stroke or spinal cord injury) was defined. RESULTS: Total aortic arch replacement was performed in 264 patients by 19 cardiovascular surgeons. Analysis revealed that the composite end point was attained more frequently when the team score was <7 ( n = 23; 29%) than >7 ( n = 35; 19%) ( P = 0.015). There was a significant difference depending on the surgeon's experience [3 = 23 (35%); 4 = 9 (22%); 5 = 26 (17%); P = 0.008] and whether he was equally experienced ( n = 9, 45%) or not as the assisting surgeon ( n = 49, 20%; P = 0.015). Logistic regression revealed age >70 years [OR 2.93 (1.52–5.66); P = 0.001], previous stroke [OR 3.02 (1.36–6.70); P = 0.007], acute type A aortic dissection [OR 2.58 (1.08–6.13); P = 0.033], previous acute kidney injury [OR 2.27 (1.01–5.14); P = 0.049] and 2 surgeons with the same experience [OR 4.01 (1.47–10.96); P = 0.007] as predictors for the composite end point. CONCLUSIONS: Total aortic arch replacement is equally safe whether an experienced surgeon carries it out or assists the procedure. A less experienced team may raise the risk for postoperative complications. Our data suggest an association of equally experienced surgeons in a team with worse outcomes than teams possessing different experience levels. Abstract : The European Association of Cardiothoracic Surgery's current consensus document recommends the frozen elephant trunk (FET) technique for total aortic arch replacement (TAR) due to its anticipatory nature for later frequently necessary distal interventions.